Modelling of concrete cover degradation caused by rebar’s corrosion – multicomponent media theory approach - Krykowski, Tomasz (Computer Assisted Methods in Engineering and Science, 2017)
This paper presents the model based on the theory of multicomponent media that allows modelling of rebar corrosion processes. The presented model extends and consolidates the dissertations that have been described in the papers [8-10]. The aim of the present work is a creation of the model consistent with the thermodynamics of multicomponent media with internal parameters, allowing description and numerical modelling of reinforced concrete structures degradation as the result of corrosion by using FEM.